Estado democrático de direito e poder jurisdicional: a fundamentação jurídica como forma de efetivação do devido processo legal e democratização do processo judicial - Martins, Juliana Matos (2016)
The question beyond this study is: is the obligation of grounds every decision consequence of due process in the context of a Constitutional State? On the way of this premise, this master degree dissertation end is the study about due process of law in a Democratic State of Law, showing how a suitable grounding have become important to the democratization of a righteous process. The first part of the study is destined to the analysis of the relation between the Democratic State of Law and the judge, when we will study the role of law interpreterapplicator conquered from constitutionalism. The second part leads the study to the due process of law itself and your application in a Constitutional State, remembering the obligation of a suitable grounds in judicial decisions. Meanwhile, we expose the obligation ground like a constitutional right, foresee on article 93, IX, merging it in a Democratic State of Law, revealing in a consequence of the due process of law. The last part, shows a new concept of the institute of grounding on the new legislation, explaining how it will work on this new scenario